Interlocking ferrocement-brick composite slab. - Thanoon, Waleed Abdulmalik (2004)

(untitled)
An interlocking composite slab for use in floor construction is disclosed, preferably for use in the construction of a floor slab in multi-storey buildings and structures. It comprises chiefly of an inverted ribbed precast ferrocement (10) interlocking with bricks (20) and in-situ ribs (21) to form a composite floor slab unit. The precast ferrocement is intended to replace formwork used in the construction of floor slab. Bricks (20) form part of the composite as it is a common commodity which offers substantial weight saving and thermal insulation properties compared to reinforced concrete.